Annual Gametogenesis Patterns in Two High-Latitude Corals, Alveopora japonica and Oulastrea crispata, from Jeju Island, South Korea - Jin-Soo Park; Keshavmurthy, S.; Subramaniam, T.; Sang-Ryul Park; Chang-Keun Kang; Kwang-Sik Choi (Springer, 2019)
Sexual reproduction in corals is pivotal for the survival of populations in the face of climate change. Off Jeju Island, which lies off the south coast of Korea, a high-latitude scleractinian coral, Alveopora japonica, has experienced a population explosion over the past couple of decades (at 5–15 m depths). A second species, Oulastrea crispata, which is generally present at high latitudes and extreme environments, has a stable population and dominates in the shallow subtidal waters of southern Jeju. This study examined the annual gametogenesis patterns of A. japonica off the north (33°24′N, 126°13′E) and south (33°14′N, 126°36′E) coasts of Jeju Island, and of O. crispata in the south. Histological analysis revealed that the oogonia and spermatogonia in A. japonica developed in separate mesenterial filaments, while the gonads in O. crispata developed in the same filament. Alveopora japonica had the same brooding period during late summer and early fall (Aug–Sep 2015) at both sites. The spawning period of O. crispata was also during late summer and early fall. Brooding in A. japonica was concordant with previous observations of its planula during the brooding period. This study provides the first data on the timing of reproduction of these two high-latitude coralsfrom Jeju Island, which may help our understanding of the population dynamics of corals in other high-latitude environments.
Keywords: Alveopora japonica; Oulastrea crispata; Planula; High-latitude; Reproductive physiology; Korea